Synthesis of 3,5-Bis(acrylaldehyde) boron-dipyrromethene and application in detection of cysteine and homocysteine in living cells - Madhu, Sheri; Gonnade, Rajesh G.; Ravikanth, Mangalampalli (Journal Of Organic Chemistry, 2013)
Synthesis, characterization, and spectral and electrochemical properties of 3,5-bis(acrylaldehyde) BODIPY are described. The compound exhibited higher selectivity toward cysteine/homocysteine than toward other amino acids and thiol-containing compounds as shown by absorption and emission titration experiments and by experiments in living cells.